Amanah Saham National Berhad's : promotional strategies and its relationship with customer motivation - Yahaya, Azizi (Science Publications, 2009)
Problem statement: Every single company needs strategies in order to survive or to become a leader in the market nowadays, therefore a study towards findings the suitable strategies for Permodalan National Berhad had been carried out. Approach: The purpose of the study was to determine the types of ASNB’s promotional strategies, to identify the level of effectiveness promotional tools used by Amanah Saham National Berhad (ASNB), to describe the correlations between ASNB’s promotional strategies with customer motivation to invest and to examine the effect of the promotional tools with the customer motivation to invest in ASNB’s products. Results: The findings from the study found that several strategies should be recommended to Amanah Saham National Berhad (ASNB). Firstly, ASNB should increase sales promotion such as high income distribution/dividend, offer scheme ‘bantuan khairat kematian’ to the investors, offer fixed and variable price as well as withdrawal or savings at any time for the investors as this can really encourage Bumiputera and non Bumiputera to invest in ASNB. Secondly, the information about PNB should be more advertise in television and newspaper since people are always see and read this two medium. The advertisement also should be more creative and attractive. Conclusion: Furthermore, PNB should hire more sales executives and hire individual agents as the strategy to boost up ASNB’s sales.